Effect of process parameters on friction stir welded joints of AA 7039. (2022) - Chauhan, Gaurav; Sahu, Mrinal; Prasad, Pyla; Paul, Atanu; Ganguly, Subhas
Abstract: Friction Stir Welding is a new welding technique for joining high-strength aluminum alloys. In the recent years, the technology has already proved its presence in various industries like automobile, aviation, railways, marine, defense etc. Aluminum and its alloys are widely acceptable in structural applications, especially, AA 7039 is widely utilized in defense and marine industries. Friction Stir Welded joints usually does not exhibit the problems associated with the conventional welding techniques. The welding joints are highly influenced by the parameters involved in their fabrication. As a result, the purpose of this research is to investigate and characterize the influence of tool rotation speed and traverse speed (feed rate) on joining efficiency. Joint having weld configuration of 1000 RPM and 28 mm/min of feed rate shows highest tensile strength of 84.27% whereas lowest strength of 51.22% is recorded for the joint fabricated with 500 RPM and 56 mm of feed rate. Microhardness and microstructural features are investigated considering mechanical characteristics.